Model pembelajaran berbasis permainan tradisional untuk keterampilan berlari dasar pada siswa sekolah dasar dengan gangguan intelektual ringan - Mustara Mustara; Fajar Vidya Hartono; Slamet Sukriadi; Marhadi Marhadi (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Students with intellectual disabilities often face barriers in developing fundamental motor skills, especially running, because of limited adaptability and slower learning processes. Previous physical education practices in special schools remain conventional and rarely offer models tailored to these students. To address this gap, this research developed a basic running movement model based on traditional games, chosen for their simplicity, cultural relevance, and ability to foster motivation and engagement. The study applied a Research and Development (R&D) approach adapted from Borg & Gall, covering preliminary research stages, planning, expert validation, limited trials, and broader implementation. Participants involved 50 students with mild intellectual disabilities from four special schools in Jakarta. Expert validation using the Content Validity Ratio (CVR = 0.7) and reliability analysis with Cronbach's Alpha (α = 0.839) confirmed that the model was valid and reliable. Effectiveness testing through pre- and post-intervention assessments significantly improved students' running abilities (t = 4.388, p < 0.05). These results indicate that the model is feasible for classroom implementation, as it enhances motor skills, increases student motivation, and provides an inclusive learning medium. Compared to previous studies, the novelty of this research lies in systematically integrating traditional games into structured running instruction for students with intellectual disabilities. The model is also low-cost, adaptable to school facilities, and promotes enjoyment in physical activity.